2022
DOI: 10.5334/gh.1134
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Imaging Utilization and Findings among Hospitalized COVID-19 Patients in Latin America

Abstract: Objectives: Describe the use and findings of cardiopulmonary imaging-chest X-ray (cX-ray), echocardiography (cEcho), chest CT (cCT), lung ultrasound (LUS), and/or cardiac magnetic resonance imaging (cMRI)-in COVID-19 hospitalizations in Latin America (LATAM). Background:There is a lack of information on the images used and their findings during the SARS-CoV-2 pandemic in LATAM.Methods: Multicenter, prospective, observational study of COVID-19 inpatients, conducted from March to December 2020, from 12 high-comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(13 reference statements)
1
0
0
1
Order By: Relevance
“…We also had a greater number of rehospitalization than reported in SEMI-COVID-19 (3.9% vs 7.3%). Deficient treatment, high comorbidities, and a poor healthcare system contributed to the higher mortality rate in LA&C. The study performed by Spina et al [33] identified similar results in mortality and comorbidities which reflected the severe circumstances of our population that could influence those rates.…”
Section: Discussionsupporting
confidence: 58%
“…We also had a greater number of rehospitalization than reported in SEMI-COVID-19 (3.9% vs 7.3%). Deficient treatment, high comorbidities, and a poor healthcare system contributed to the higher mortality rate in LA&C. The study performed by Spina et al [33] identified similar results in mortality and comorbidities which reflected the severe circumstances of our population that could influence those rates.…”
Section: Discussionsupporting
confidence: 58%
“…A magnitude do acometimento pulmonar, assim como a associação com outros achados de imagens (consolidação, espessamento septal e derrame pleural) e comorbidades, estiveram relacionados a pior prognóstico do paciente, com maior frequência de óbitos nos grupos com essas alterações com relação aos pacientes que não apresentaram. O que pode ser explicado por denotarem maior gravidade ao quadro do paciente, visto que esses achados sugerem um prejuízo à expansão e ventilação pulmonar, levantando a hipótese sobre o impacto que a fisioterapia respiratória poderia ocasionar na evolução da internação 2,8 .…”
Section: Discussionunclassified